TEACHING QUESTION WORDS FOR ADULT LEANERS BY USING THE PICTURES OF SOMEBODY POPULAR AS A TEACHING MEDIA - Ali Amran (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
This study investigates and predicts the learners difficulties in using those question word : what, when, where, why, who, whose, whose, whose, which and how through out the pictures ol‘ somebody. Most new beginners of English language hope to speak the language they learn as soon as they can, without considering over about the langauge grammar, particularly in applying those question words.